Editorial Vol.1(1) - Adhikari, Rameshwar (Applied Science and Technology Annals, 2020)
The ongoing coronavirus disease 2019 (COVID-19) pandemic caused by a novel coronavirus, named as severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), is affecting every societies throughout the world. In these odd times of global crisis, we put our efforts to publish a first-ever peer-reviewed journal of the Research Centre for Applied Science and Technology (RECAST), officially known as the Applied Science and Technology Annals (ASTA), to disseminate the scientific information and knowledge in broader field of science and technology to the readers. This first issue of ASTA, a COVID-19 special issue, provides comprehensive information on the history, epidemiology, diagnosis and treatment options of COVID-19. It also includes the governmental strategies to minimize the impacts of the pandemic on societies, and economies in the country along with the importance of local knowledge and technologies to address the challenges posed by the pandemic.The COVID-19, which originated in Wuhan city of China in last December, has infected millions of people worldwide and claimed more than half millions of lives. With unprecedented damage to the global economies, and increased stigmatization and xenophobia against particular communities, the pandemic is far more than a health crisis. Considering the overall health and psychosocial impacts of COVID-19, it can be assumed that the impacts of the pandemic are not less than the effects of the past World Wars. Moreover, the pandemic is forcing us to revisit our critical thinking and reconsider our ‘normal’ activities in a sustainable manner.Despite its high infectivity and fatality rates across the world, the COVID-19 related fatality in Nepal seems to be comparatively low. One can argue that early measures such as nationwide lockdown implemented by the government of Nepal may have contributed to the current scenario of the pandemic in the country. However, it is unclear whether the current situation is due to a less-virulent strain of the virus circulating in Nepal. The WHO guidelines including increased testing capacity, contact-tracing, quarantine and treatment to minimize the impact of the COVID-19 was not efficiently implemented by the government from the beginning. Our capacity to accelerate the laboratory diagnosis of COVID-19, and conduct research on the genetic makeup of the virus was severely limited by the governmental inability to mobilize the resources and skilled professionals available in the country. However, very efforts of the National Innovation Center (NIC) in collaboration with RECAST has led to the development of personal protective equipment (PPE) and other needy tools locally for the frontline healthcare professionals and security personnel. Thus, it is fair to say that the current situation of the COVID-19 in Nepal is due to the cumulative efforts of Nepal Government, frontline healthcare workers, laboratory professionals, technicians, scientists, researchers, volunteers, the general public and the leaders of the society. We hope that the expert opinions, and scientific findings presented in this  special issue of ASTA would provide guidance for the policy makers to formulate and implement effective strategies to combat the COVID-19 pandemic in Nepal and provide a competent disaster preparedness plan to cope with future pandemics. Our success in innovating healthcare tools and materials at the local level (with coordination from various national and international organizations) in times of crisis would hopefully motivate Nepal government to invest more in scientific research and development.We are grateful to all authors and reviewers for your contributions to the journal. We extend our sincere thank you to all well-wishers and those who have supported us directly or indirectly. It would be impossible to publish this journal without your contributions and support.  We hope your continued support in our new journey of science communication.The Editorial Board June, 2020, Kathmandu, Nepal